Upaya Peningkatan Kompetensi Guru dalam Menyusun RPP melalui Supervisi Akademik dengan Tehnik Workshop di SD Negeri Tambakrejo 02 UPTD Pendidikan Kecamatan Gayamsari Kota Semarang Tahun Pelajaran 2016/2017 - Murniati Murniati (Universitas PGRI Semarang, 2019)
The results of the study are based on the results of data analysis and discussion of cycle I through cycle II that have been carried out by researchers, the conclusions of this study are as follows: (1) Actions of cycle I, the results of the preparation of lesson plans made by the teacher turned out to be better than the results of the initial conditions. This was proven at the pre-cycle meeting, the initial conditions before PTS was held there were only 5 teachers who made lesson plans out of 8 teachers in SDN Tambakrejo 02 or only 62% and good quality lesson plans were only 2 RPPs or 40%. evaluated the teacher data obtained which made the RPP increased to 7 people. From 7 RPPs that have been made by teachers, the quality has increased to 5 RPPs with good quality. Based on the results of the first cycle, the researchers continued the second cycle of research. After the action in cycle II, there was an increase in the number of teachers making RPP to 8 people, while good quality RPPs became 7 RPPs, 8 SDN Tambakrejo 02 teachers were able to make RPPs and only 1 RPPs were made. not yet categorized as good quality. In other words, the number of teachers who have made lesson plans increased to 100% and RPP with good quality increased to 88% so the researchers concluded that academic supervision with workshop techniques carried out by researchers could improve the ability of teachers in SDN Tambakrejo 02 in Making RPPs as preparations for implementing learning.